Survei Minat Siswa MTs Raudhatut Thalibin Kolor Sumenep terhadap Ekstrakurikuler Pencak Silat - Muhammad Arif; Winda Nuraisyah; Rendra Kusuma (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to describe the level of interest of students at MTs Raudhatut Thalibin Kolor Sumenep in pencak silat extracurricular activities. Student interest is a determining factor in the success of extracurricular programs as it directly affects participation rates and program sustainability. This study employed a quantitative descriptive approach using a survey method. The research population consisted of all 20 students actively participating in pencak silat extracurricular activities, with total sampling as the sampling technique. Data were collected using a questionnaire adopted from Atmoko (2018) with a validity coefficient of 0.827 and a reliability coefficient of 0.929, analyzed using descriptive percentage analysis. The results indicated that intrinsic factors including attention (75%), enjoyment (87.5%), and activity (95%) were in the good to very good category, with the activity indicator achieving the highest percentage. Extrinsic factors also showed good results, particularly regarding the role of teachers or coaches (81%) and facilities (77.5%), while family support still required improvement. Overall, students' interest in pencak silat extracurricular activities was categorized as good, with intrinsic factors as the most dominant. Increasing family involvement and optimizing supporting facilities are the main recommendations for future program development.